- #1

- 251

- 0

and relpace the resulting formula by an equivalent which does not involve ## \neg, \vee, \wedge ##

attempt:

## \neg ([\neg (p\wedge \neg q)]\wedge \neg r) = \neg \neg (p \wedge \neg q) \vee \neg \neg r ##

## = (p \wedge \neg q) \vee r ##

## = (p \vee r) \wedge (\neg q \vee r) = \neg ((p\vee r) \implies \neg (\neg q \vee r)) ##

## = \neg ((p \vee r) \implies \neg \neg q \wedge \neg r) = \neg ((p \vee r) \implies q \wedge \neg r) ##

## = \neg (\neg p \implies q \implies \neg (\neg q \implies r)) ##

not sure if this is correct so far, and if it is, where to go from here